cosec square theta -cot square theta =sec square theta -tan square theta
Answers
Answered by
1
here it is I am send a photo okay.
take rhs
sec2-tan2=1/cos2-sin2/cos2
1-sin2/cos2
cos2/cos2=1
TAKE LHS
cosec2-cot2=cosec2-(-1+cosec2)
cosec2+1-cosec2=1
LHS=RHS
take rhs
sec2-tan2=1/cos2-sin2/cos2
1-sin2/cos2
cos2/cos2=1
TAKE LHS
cosec2-cot2=cosec2-(-1+cosec2)
cosec2+1-cosec2=1
LHS=RHS
Attachments:
![](https://hi-static.z-dn.net/files/d75/7a67e59b6cca9580c137ee941dddff2c.jpg)
krishnarajsinh:
done
Similar questions